Effect of Bacillus amyloliquefaciens and Pseudomonas migulae on the growth of gooseberry (Physalis peruviana L.) seedlings: Rizobacterias promotoras en plántulas de uchuva (Physalis peruviana L.). - Beltrán-Acosta, Camilo Rubén; Zapata-Narváez, Yimmy Alexander; Millán-Montaño, Duván Albeiro; Díaz-García, Andrés (Agronomía Mesoamericana, 2022)
Introduction. The use of plant growth-promoting bacteria can be an alternative to be integrated as a management strategy of cape gooseberry crop through their incorporation in seedling stages, allowing to obtain more vigorous seedlings that can tolerate biotic and abiotic stress at the time of transplant. Objective. To evaluate the plant growth promoting activity and endophytic capacity of Bacillus amyloliquefaciens Bs006 and Pseudomonas migulae Pf014 inoculated during the seedling stage of cape gooseberry (Physalis peruviana L.). Materials and methods. In a randomized complete block design with three replications, an experiment was carried out from April to May 2018 in a greenhouse located at the Tibaitatá Research Center, Mosquera, Colombia. Bacteria were inoculated separately in the substrate at 1 x 108 UFC mL-1. Physiological variables such as dry biomass of the root, stem, and leaves (g), final length (cm), leaf area (cm2), and the number of leaves were analyzed; additionally, its endophytism was verified by evaluating the colonization of the plant tissue. Results. B. amyloliquefaciens Bs006 stimulated seedling growth at different levels, exhibiting greater promotion capacity than P. migulae Pf014, since it increased plant length by 34 %, and stem and root growth by 59 % and 16 %, respectively; also, increase in dry root biomass by 178 %, stem by 161 %, and leaves by 96 % was found. In addition, bacteria were isolated from the interior of plant tissues, demonstrating their endophytic behavior. Conclusions. The positive response in all the agronomic variables evaluated with the application of B. amyloliquefaciens Bs006, indicates that this rhizobacterium can be integrated into the cape gooseberry production scheme, helping to enhance crop production.